Uzbek Folk Epic. About The Epics Of The Series” Goroglu" - Gulumov Maqsud Uktam o‘g‘li (Genius Journals, 2024)
this article includes observations on the origin of the “Gooroglu” series of epics, the region of their distribution, the study of epics within the series. In this regard, the variants sung by Uzbek Bakhshis of the “Gooroglu” series of EPICs were made the main object.
Keywords: Gooroglu; folklore; saga